Investigating the Role of MODIS Leaf Area Index and Vegetation-Climate Interaction in Regional Climate Simulations over Asia - Jingyong Zhang; Dong-Hyun Cha; Dong-Kyou Lee (Terrestrial, Atmospheric and Oceanic Sciences, 2009)

(untitled)
Four year long climate simulations using the Seoul National University, regional climate model have been per formed to assess the role of the MODIS Leaf Area Index (LAI) and inter active LAI in influencing Asian climate. The control experiment employs the fixed monthly LAI ac cording to the original land surface model. Another additional simulation re places the LAI by 4-year mean MODIS climatology. The last two integrations both al low the LAI to interact with the at mo sphere, but adopt two different simple parameterization schemes.